Towards Excellence in Public Administration Education and Training: an African and South African Experience - Hendri Kroukamp (Central European Public Administration Review)
Not only did globalization bring about profound changes to public administration worldwide, but it also challenged the implementation of the New Public Management (NPM) paradigm in terms of service delivery, posing the question whether public administration must reinvent itself to address these challenges more effectively. Many changes that have been implemented in the public sector have not been based on evidence that change would benefit those using the services, those working in them and the community as a whole. Taking cognizance of especially the current African and South African higher education environment, it became clear that in order to move towards excellence in public administration education and training, the curricula must be amended and should the focus be on particular skills to be transferred to learners to address the above- mentioned situation. The question arises whether the nature of these developments would be relevant to the needs of both the learner as well as public institutions.